Analisis Hasil Rekondisi Mesin Frais Aciera F3 Terhadap Pengujian Geometris, Uji Jalan dan Uji Getaran - Fajar Aswin; M Riva’i; Dedy Firmansyah; Akmarul Umam (Manutech : Jurnal Teknologi Manufaktur, 2018)
The recondition of the Aciera f3/07 milling machine has been done to restore the machine condition to be ready for use. The machine was damaged and caused the machine to be unable to operate and made electrical and mechanical components fail. The feasibility of the machine is tested to see the achievement of the purpose of machine reconditioning. This paper aims to see the results of the geometric testing of the machine compared with the results of running test and the vibration measurement of the machine parts. This study uses an experimental method, where damage to the machine will be identified and the damage will be immediately carried out repairs or replacement of spare parts. Furthermore, machine performance was testing including machine geometry testing, vibration testing and running test in accordance with ISO-1708 standards. The test results show that there is no significant differencebetween the results of the geometric precision testing of the machine on vibration testing and road testing. This can indicate that all three tests can be used as a reference in validating the results of machine repair, especially repairing irregularities in the geometric accuracy of the Aciera F3 milling machine.